Caught in a "Triple Bind": How the Physical Body Experiences Paradox - Greenslade-Yeats, James; Mharapara, Tago; Ravenswood, Katherine; Clemons, Janine; Staniland, Nimbus (SAGE Publications, 2026)
What does it mean to “embody” paradox? In this paper, we adopt a "literal" interpretation of this question, examining how physical bodies experience, enact, and respond to knotted paradoxical tensions within the context of interpersonal and structural power relationships. We draw on a qualitative study of self-employed, community midwives (N=47) whom we interviewed jointly with their family members (N=51). Our findings paint a rich picture of how midwives experience knotted tensions through embodied polarities of presence-absence and energy-fatigue. We also elucidate how paradox knotting and power relations combine to transform midwives’ experiences of embodied tensions into a restrictive “triple bind,” where physical depletion adds a “third dimension” of material constraint to the interpersonal and structural constraints that characterize double binds. We detail three response patterns midwives use in attempting to navigate the triple bind, highlighting both the importance and limits of interpersonal support and gendered role negotiations. Our work advances understanding of paradox as a non-rational, embodied phenomenon, the navigation of which may require radical systemic change.
Keywords: 350503 Human resources management; 3507 Strategy, management and organisational behaviour; 350709 Organisation and management theory; 1503 Business and Management; ambiguity; data analysis; domination; embodied paradox; gender performativity; interpretive; paradox; paradox knotting; paradox theory; power; resistance